A new robotic horseback-riding simulator for riding lessons and equine-assisted therapy. (4th July 2018) - Lee, Wonsik; So, Byung-Rok; Lee, Youngdae; Moon, Chanwoo
Robotic horseback-riding simulators have been successfully used as a substitute for real horses in areas of therapy, riding lessons, fitness, and entertainment, and several have been developed. However, recent research has illuminated significant differences in motion, response, and feel between a real horse and a simulator, which may result in incorrect posture and muscle memory for the rider. In this study, we developed a hybrid kinematic structure horseback-riding simulator to provide more realistic motion than currently available ones. The basic system has 4 degrees of freedom and provides a base motion platform. An additional revolving system with 2 degrees of freedom is mounted on the base platform. Real horse motion data were captured, normalized, filtered, and fitted to provide the motion trajectory. Furthermore, active neck, saddle, and tail mechanisms were implemented to provide realistic simulation. For interactive horse riding, bridle and beat sensors were included to control the simulator motion and a large screen was installed for virtual reality effect. Expert tests were conducted to evaluate the developed horseback-riding system, the results of which indicated that the developed simulator was considered sufficient for riding lessons and therapeutic use.